Revitalizing Institutional Policy Grounded on Work-Life Balance of Employees in a Catholic Higher Education Institution: A Cross-sectional Study - Bueno, David; Reyes, Amelia Cecilia; Aquino, Carlota (JPAIR Multidisciplinary Research, 2017)
It presupposes that workers must deal with the challenging demands as they confer between spheres of "life" and "work". The study determines the current Work-life Balance (WLB) practices and policies as basis for institutional policy reformulation in a Catholic Higher Education Institution (HEI). The researchers utilized the descriptive cross-sectional design of research to obtain information concerning the analysis of the work-life balance of employees using survey-questionnaire at a given time in an academic year. The participants of the study were school administrators and faculty members in one private higher education institution in the Philippines with full-time status during the Academic Year 2015-2016. The survey- questionnaire for work-life balance (WBL) was modified from "Better Work-life Balance Survey-Employees" of the University of Queensland in 2005. Descriptive and inferential statistics such as Percentage, Weighted Mean, Standard Deviation, and Pearson’s Product Coefficient Correlation were used for a more efficient, effective and accurate analysis of data. The work-life balance related activities of employees are sometimes at risk. Work-life related policies on leave arrangements are being viewed by employees in various ways in the organization. Parenting and pregnancy related policies are also evident. Furthermore, various work arrangement related-policies are also enjoyed by the employees. Additional provisions regarding work are also evident. Thus, there is moderate impact work-related activities and policies on the personal life of employees.